The ethics of retaliatory violence in Athenian tragedy - Allan, W (Brill Academic Publishers, 2013)
This article focuses on the presentation of retaliatory violence in Athenian tragedy. It suggests that such tit-for-tat violence is characterized as problematic from the earliest Greek literature onwards, but also stresses the continuing importance of anger, honour, and revenge in classical Athenian attitudes to punishment and justice. With these continuities in mind, it analyses the new process by which punishment and justice were achieved in Athens, and argues that the Athenians’ emphasis on the authority of their laws is central to understanding tragedy’s portrayal of personalized vengeance and the chaos that ensues from it. Though (for reasons of space) it focuses on only a selection of plays in detail (A. Eu., S. El., E. El., Or.), the article adduces further examples to show that the same socio-historical developments are central to the portrayal of retaliatory violence throughout the genre, and ends by considering how tragedy, in depicting revenge as problematic, offers a more positive alternative to such violence which does justice to the emotional and social needs of its audience.